Persuasive Language In Selected Speeches Of Tun Dr. Mahathir Mohammad - Alkhirbash, Abdul Rahman (2010)

(untitled)
It is clearly observed that the last quarter of the twentieth century has witnessed renewed interest in understanding the nature of persuasion and the study of language as a tool to achieve persuasion. There has been an interest to develop the study of rhetoric to become an appropriate tool peculiar to the changes of modern life. The present study sought to explore language and persuasion in the speeches of a leading Malaysian politician. It conducted a rhetorical analysis of selected speeches of Dr. Mahathir (the fourth Prime Minister of Malaysia) to identify and interpret his language use as a means to persuade and convince his audience to accept or follow a specific course of action. Of particular concern in this study was the question of what rhetorical devices Dr. Mahathir used and how he utilized them to influence his audience. Specifically, this research attempted to identify and describe the rhetorical devices and speech acts used by Dr. Mahathir to persuade his audience. Based on Fairclough’s approach of discourse analysis, Aristotle’s understanding of the three appeals of persuasion and Searle’s speech act theory, this study explored logos, ethos, pathos and speech acts as a means of persuasion demonstrating how they were applied to persuade the audience. The study also identified other linguistic devices which were used as supportive strategies such as the use of parallelisms, repetitions, rhetorical questions, metaphors, and enthymemes. The findings revealed that Dr. Mahathir merged logical, emotional and ethical proofs to address his audience’s minds and hearts simultaneously. Logical proofs were used via providing reasons, facts, past events, and statistics. They were consolidated by supportive techniques such as enthymemes, examples, parallelisms and metaphors to add clarity and conciseness. His rhetorical messages were not devoid of emotion. Emotional proofs were utilized to arouse different types of feelings such as anger, sympathy, jealousy, resentment and compassion. Together, logos and pathos worked to projects his ethos. The utilization of logos reflected his competence, knowledge and awareness in the addressed issues. His pathos reflected his goodwill and concern for the welfare of others. His argument and messages projected him as competent, sincere, well informed, even-handed, and concern of others’ welfare. Assertives and directives were also used by Dr. Mahathir as persuasive devices. Assertives were used to emphasize and confirm facts or to assert beliefs whereas directives were used to suggest, recommend or command to encourage his listeners to perform actions and influence their attitudes. The study concluded that various rhetorical devices mainly logos, pathos, directives and assertives worked collaboratively to project Dr. Mahathir’s ethos as a strong element of his persuasive discourse.